843 Paradoxical Waking Hypoxemia that Improves with Sleep. (3rd May 2021) - Cho, Jessica; Dai, David; Fung, Constance
Abstract: Introduction: We present a case of paradoxically worsened hypoxia during wake phase of polysomnography while undergoing a CPAP titration study. Nighttime hypoxemia is a common feature in obstructive sleep apnea, due to obstructive events that manifest while sleeping. Excluding OSA, there remains an extensive differential for disease processes that cause hypoxemia while asleep; however, none of these processes can explain waking hypoxemia that improves upon sleeping. Report of case(s): A 70 year old male with severe OSA diagnosed by home sleep test (REI 46.5, nadir O2=76%) underwent polysomnography with PAP titration and demonstrated several hours of interrupted sleep without hypoxia and minimal obstructive events on CPAP 9–13 cmH2O. During the study, while awake at CPAP of 14 cmH2O, he developed hypoxia to mid-high 80s and supplemental oxygen bleed in was added starting at 3L and increased to 5L during a prolonged period of wakefulness. On CPAP 15 cmmH2O with 5L bleed-in, the patient fell asleep and oxygen saturation again increased to low 90s. He underwent an extensive workup for other cardiopulmonary causes of hypoxemia, with pulmonary function testing showing moderate obstructive ventilatory defect and mild DLCO impairment. An echocardiogram with saline contrast bubble study was relatively unremarkable, without evidence of right to left shunting. He underwent a chest CTA which was negative for pulmonary embolism, though it did reveal an enlarged pulmonary artery consistent with pulmonary hypertension. His chronic hypoxemia was treated with 2L supplemental oxygen during the day and bleed-in with CPAP at night. Conclusion: Though nocturnal hypoxemia is common with OSA, polysomnography with paradoxical hypoxemia during wake phase has not been reported. Notably, the patient was without prolonged hypoxia during his sleep phase while on CPAP treatment with minimal apneic/hypopneic events. Pulmonary hypertension can also present as nocturnal hypoxemia, but it should worsen with sleep, rather than improve. There are case reports of right to left shunting worsened by PAP, though his hypoxemia persisted despite PAP. His paradoxical worsening hypoxemia with wakefulness is still unexplained. Support (if any):